Brain Neuroendoscopy: Experience in Experimental Models and Clinical Application - Alvarez Peña, Carlos (2000)
OBJECTIVE: Experimental models (EM) design to acquire brain neuroendoscopy (BNE) skill to be applied on patients. MATERIAL AND METHODS: Study performed in three phases. For the first two -design and training- we used bovine and human coipses randomly assigned to groups A and B according to physiological sodium chloride solution (SCS) volume needed to produce satisfactory hydrocephalus to perform BNE. During phase three, BNE was performed in 5 patients with brain pathology confirmed by CAT or NMR. RESULTS: SCS volume needed for satisfactory BNE in the bovine EM was usually 70 mL (p< 0,01). In human EM, artifitial hydrocephalus was obtained with 150 mL of SCS (p< 0,0 l). BNE was used as a diagnostic and therapeutic tool. Post BNE complications consisted in hallucinations, fever and memory impairment, that responded well to symptomatic therapy. CONCLUSIONS: EMs designed for this study were useful tools for BNE leaming. Training in EM for BNE is essential before its application to human beings.